2006
DOI: 10.1002/bem.20186
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 50 Hz magnetic field on sex hormones and other fertility parameters of adult male rats

Abstract: The effects of an extremely low frequency (ELF) magnetic field on the sex hormones and other fertility parameters of adult male Sprague-Dawley rats were investigated. Adult male rats were exposed to a 50 Hz sinusoidal magnetic field at approximately 25 mT (rms) for 18 consecutive weeks. There were no significant effects on the absolute body weight and the weight of the testes of the exposed rats. However, the weights of seminal vesicles and preputial glands were significantly reduced in the exposed male rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 26 publications
7
71
1
Order By: Relevance
“…From Table 1, there is no significant difference in the mean body weights either between groups 1 and 2 (295.34 ± 13.67 g and 292.72 ± 12.02 g, respectively) or between groups 3 and 4 (329.05 ± 28.95 g and 324.75 ± 25.61 g, respectively) suggesting that there is no effect of MF on the apparent body weight. These results were similar to works reported by Al-Akhras et al (2006). It is clear that the time factor in this work (21 days of exposure) was not long enough to produce a change in the body weight.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…From Table 1, there is no significant difference in the mean body weights either between groups 1 and 2 (295.34 ± 13.67 g and 292.72 ± 12.02 g, respectively) or between groups 3 and 4 (329.05 ± 28.95 g and 324.75 ± 25.61 g, respectively) suggesting that there is no effect of MF on the apparent body weight. These results were similar to works reported by Al-Akhras et al (2006). It is clear that the time factor in this work (21 days of exposure) was not long enough to produce a change in the body weight.…”
Section: Resultssupporting
confidence: 92%
“…Studies have shown several evidences related to EMF and their effects on physiological systems (Fadel et al 1994 andMcCaig et al 2004). During recent decades much interest has centered on power lines and their possible effects on health including erythrocyte properties and heart functions (Fadel et al 2003), cell stress (Tokalov and Gutziet 2004), reactive oxygen species and free radicals (Seyhan et al 2006), male and female reproduction and fertility (Al-Akhras et al 2006). The effects of ELF-EMF on the male reproduction are receiving heightened interest because human male fertility in the 20 th century was diminished; human sperm count in 1940 was nearly two-fold compared to the sperm count in 1990 (Giwereman et al 1993).…”
mentioning
confidence: 99%
“…Similar studies revealed that the reduced weight of seminal vesicle and prenuptial glands, along with decrement of testicular sperm count and testosterone levels scrutinized in adult male rats exposed to 50 Hz of 25 μT MF for 18 consecutive weeks [15]. Hong et al [16] also observed that DNA strand breakage was induced in testicular cells and abnormal condensation of sperm chromatin structure was increased in mice exposed to 50 Hz of 0.2 mT or 6.4 mT EMF for 4 weeks.…”
Section: Introductionmentioning
confidence: 57%
“…EMFs were associated with an increase in childhood leukemia, adult brain cancer, miscarriage and fertility in both male and female [1,7]. Radiation effects on salivary glands are of particular interest, where the altered composition of saliva results in distress, often irreversible complications such as oral dryness, nocturnal oral discomfort, and susceptibility to oral infections and dental caries [8].…”
Section: Introductionmentioning
confidence: 99%